TINJAUAN ELEMEN VISUAL PADA PERANCANGAN VIDEO “PERJALANAN FESTIVAL JAZZ DI INDONESIA” - Rina Setia Wardani; Christophera Ratnasari Lucius (JURNAL EDUCATION AND DEVELOPMENT, 2024)
Prambanan Jazz Festival is a music festival that is held annually in the courtyard of Prambanan Temple, this event is highly anticipated by the community, both teenagers and adults. This event is international in scale, so many audiences from various regions and countries flock to attend this event. This research consists of designing a video about the journey of jazz music festivals in Indonesia presented in infographics. The purpose of this research is to provide information and knowledge related to the implementation of the jazz music festival to the audience of the Prambanan Jazz music festival held at Prambanan Temple. The research method uses a qualitative approach with a field note data collection method that the author gets from reliable articles and journals. The result of this research is an infographic video about the journey of jazz music festivals in Indonesia including Java Jazz Festival, Prambanan Jazz Festival, Jazz Goes To Campus, and Jazz Gunung Festival.